Malign melanoma on the irradiation field after adjuvant treatment of breast cancer: A case report - Karao?lu, Aziz; Saral, Yunus; Elkiran, Emin T.; Aygen, Bilge; Topkan, Erkan; Çobano?lu, Bengü; Güler, Nilufer (My University, 2006)
Patients with breast cancer have a chance of long-term survival. All subsets of breast cancer patients are therefore at risk of developing second malignancies. Melanomas are among to the infrequent nonepithelial second neoplasm. We report an developed malign melanoma which was appeared in the irradiation area after 11 months of adjuvant treatment.
Keywords: Breast cancer; Irradiation; Malign melanoma